2011
DOI: 10.1007/s10658-011-9753-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming with Serratia plymuthica and Pseudomonas chlororaphis to control Leptosphaeria maculans in different oilseed rape cultivars

Abstract: The efficacy of a seed treatment of oilseed rape (OSR) (Brassica napus) with the rhizobacteria Serratia plymuthica (strain HRO-C48) and Pseudomonas chlororaphis (strain MA 342) applied alone or in combination against the blackleg disease caused by Leptosphaeria maculans was tested with different cultivars. Seeds were soaked in bacterial suspensions (bio-priming) to obtain log 10 6-7 CFU seed −1 . Cotyledons were inoculated with a 10 ul droplet of L. maculans spore suspension of log 10 7 spores ml −1 and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…Seed treatments of oilseed rape ( Brassica napus L.) directed against the blackleg disease caused by L. maculans have shown that the rhizobacteria Serratia plymuthica Breed et al 1948 and P. chlororaphis can reduce disease severity by 71.6 and 54% respectively. However, with the application of these two rhizobacteria in combination, using the biopriming technique, the effectiveness of the combined treatment was not superior to that with S. plymuthica alone . In another study, a greater reduction in disease infestation under field conditions was provided by the combined treatments of S. plymuthica and Clonostachys rosea f. catenulata (J.C. Gilman & E.V.…”
Section: Treatment Of Different Pathosystemsmentioning
confidence: 99%
“…Seed treatments of oilseed rape ( Brassica napus L.) directed against the blackleg disease caused by L. maculans have shown that the rhizobacteria Serratia plymuthica Breed et al 1948 and P. chlororaphis can reduce disease severity by 71.6 and 54% respectively. However, with the application of these two rhizobacteria in combination, using the biopriming technique, the effectiveness of the combined treatment was not superior to that with S. plymuthica alone . In another study, a greater reduction in disease infestation under field conditions was provided by the combined treatments of S. plymuthica and Clonostachys rosea f. catenulata (J.C. Gilman & E.V.…”
Section: Treatment Of Different Pathosystemsmentioning
confidence: 99%
“…Seeds were immersed in bacterial suspensions (10 7 -10 9 cfu ml -1 in 2% methylcellulose, pH 7.0) for 60 seconds (Abuamsha, Salman, & Ehlers, 2011). Seeds were sown in peat moss vermiculite mix (2:1, v/v) at the above mentioned conditions.…”
Section: Pathogenicity Of Bacteria To Host Plant (Wtermelon)mentioning
confidence: 99%
“…The experimental results have proven that the tested PGPF, promoted growth and induced systemic resistance (ISR) in sunflower plants against the downy mildew disease caused by P. halstedii, due to their growth-promoting and biocontrol abilities. Abuamsha et al (2012) observed that the efficacy of a seed treatment of oilseed rape (OSR) ( Brassica napus) with the rhizobacteria Serratia plymuthica (strain HRO-C48) and Pseudomonas chlororaphis (strain MA 342) applied alone or in combination against the blackleg disease caused by Leptosphaeria maculans was tested with different cultivars. Seeds were soaked in bacterial suspensions (bio-priming) to obtain log 10 6-7 CFU seed −1 .…”
Section: Bio Priming With Respect To Disease Resistancementioning
confidence: 99%